Endogenous SLPI contributes to the regulation of inflammatory responses in peritoneal macrophages by modulating MMP-9 production - Tyshchenko, Mariia; Pocałuń, Natalia; Kwiecińska, Patrycja; Cichy, Joanna; Wilk, Mieszko M.; Oleszycka, Ewa (Frontiers in Immunology, 2025)
Secretory leukocyte protease inhibitor (SLPI) is described as a potent regulator of inflammation and tissue homeostasis with pleiotropic functions. It has been shown to inhibit pro-inflammatory responses in myeloid cells. However, its expression patterns and specific functions in different monocyte and macrophage populations remain poorly understood. Therefore, we investigated its expression patterns in murine tissue macrophage populations by analysis of publicly available datasets and flow cytometry. Among various tissues, peritoneal macrophages were identified as a major source of SLPI, suggesting the highest impact of this inhibitor on their physiological and pathophysiological functions. To elucidate the role of SLPI in the inflammatory response, SLPI-deficient mice were used. First, the response to LPS was compared in resident and thioglycolate-recruited peritoneal macrophages. Moreover, we evaluated the role of SLPI in an in vivo mouse model of LPS-induced septic shock. Results demonstrated that while the lack of SLPI did not affect pro-inflammatory cytokine production in activated resident macrophages, it regulated the production of matrix metalloproteinase-9 (MMP-9). Similar results were observed in thioglycolate-elicited and LPS-activated peritoneal macrophage populations, further highlighting the link between SLPI and MMP-9. Furthermore, in vivo LPS-induced changes in SLPI expression were evident among various myeloid populations, including monocytes. Loss of SLPI also influenced the frequency of blood monocyte populations in this model. Overall, these findings highlight a specific role for SLPI in regulating MMP-9 in response to LPS both in vitro and in vivo and suggest that SLPI might play a role in tissue remodeling orchestrated by macrophages.